Changes in Erythrocytes in 88 Hyperthyroid Cats - Olga Gójska-Zygner; Grzegorz Kotomski; Joanna Gajger; Luke J. Norbury; Wojciech Zygner (Animals)
Background: There is only a limited number of studies that show alterations in erythrocytes in feline hyperthyroidism. Discrepancies between the findings of these studies may be caused by the presence of concurrent diseases and the use of various haematological analysers. Methods: This study analysed changes in red blood cells (RBCs) in 88 hyperthyroid cats without concurrent diseases, to identify associations between observed changes and to assess the influence of serum thyroxine (T4) concentration, cat age, and sex, on RBC changes. Results: Among the eighty-eight hyperthyroid cats, erythrocytosis was observed in twelve, anaemia in four, macrocytosis in two, and microcytosis in three. Three of the four cases of anaemia probably resulted from concurrent unrecognised disease. Interestingly, all cases of microcytosis were recognized in cats that had erythrocytosis. This study identified a moderate negative correlation between RBC count and mean corpuscular volume (MCV; r = −0.57, p < 0.001). Concluding, it appears that erythrocytosis may be a response to the development of microcytosis. The correlation between RBC count and MCV in hyperthyroid cats may result from the increased action of hepcidin and erythropoietin coupled with the decreased action of thyroid-stimulating hormone (TSH).